FAKTOR JENIS KELAMIN DALAM HASIL BELAJAR MAHASISWA FAKULTAS TARBIYAH IAIN WALISONGO SEMARANG - Choirun Nisa, Lulu (Universitas Ahmad Dahlan, 2012)
Gender factor as one of the factors that affect the learning process and learning outcome should be accommodated in the learning process. Therefore, please note the significance of differences in learning outcomes based on gender differences. Faculty of Tarbiyah have heterogeneous characteristics of courses, ranging from religious studies program, science, and language. Studies on student results shows that students learning outcomes male students better than female students on Tadris Mathematics Study Program. As for Islamic Education study program, Arabic Education, Islamic Education and Physics Tadris female student results are better than student learning outcomes of men. As for the Tadris English, Tadris Chemistry, Tadris Biology and MI Teacher Education data processing results showed no significant differences.